Application Of Defect Detection In Gluing Line Using Shape-Based Matching Approach - Harun, Mohamad Haniff; Mohd Annuar, Khalil Azha; Noordin, Aminurrashid; Che Hasan, Mohd Hanif; Mohd Ab Halim, Mohd Firdaus; Saealal, Muhammad Salihin; Ibrahim, Muhammad Fareq (2015)
This paper investigates various approaches for automated inspection of gluing process using shape-based matching application. A new supervised defect detection approach to detect gap defect, bumper defect and bubble defect in gluing application is proposed. The creation of region of interest for important region of the object is further explained. The Correlation algorithm to determine better image processing result using template matching techniques is also proposed. This technique does not only reduce execution time, but also produce high accuracy in defect detection rate. The recognition efficiency will achieve more than 95% with defect’s data for further process.